2000
DOI: 10.1080/00288233.2000.9513424
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of stream phosphorus in a New Zealand high‐country agricultural catchment

Abstract: Spatial and temporal variability of stream total phosphorus (TP) concentrations and loadings was evaluated over a year in a high-country agricultural catchment. One storm event was also sampled at the inflow to a lake. An upland tributary had the highest median concentration (0.064 mg T 1 ), but the maximum (0.614 mg I" 1 ) occurred at the inflow during the storm. Values near the lake surface were low but increased with depth in summer. There was a large difference between two streams, and values exceeded wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
4
2
Order By: Relevance
“…Basefl ow, although it does not generally contain high P concentrations, can act as a constant background source of P , and contribute substantially to cumulative P loads (Hooda et al, 1999;Caruso, 2000;Maguire and Sims, 2002;Hively et al, 2006). A lumped export coeffi cient approach is used to model basefl ow P loss:…”
Section: Dissolved Phosphorus Loss Associated With Basefl Owmentioning
confidence: 99%
See 1 more Smart Citation
“…Basefl ow, although it does not generally contain high P concentrations, can act as a constant background source of P , and contribute substantially to cumulative P loads (Hooda et al, 1999;Caruso, 2000;Maguire and Sims, 2002;Hively et al, 2006). A lumped export coeffi cient approach is used to model basefl ow P loss:…”
Section: Dissolved Phosphorus Loss Associated With Basefl Owmentioning
confidence: 99%
“…Baseflow, although it does not generally contain high P concentrations, can act as a constant background source of P (McDowell et al, 2001), and contribute substantially to cumulative P loads (Hooda et al, 1999; Caruso, 2000; Maguire and Sims, 2002; Hively et al, 2006). A lumped export coefficient approach is used to model baseflow P loss: LnormalB,normalt=μnormalBBnormaltwhere L B,t is the DP load (kg d −1 ) in baseflow, B t is the VSLF predicted baseflow volume at the watershed outlet (m 3 d −1 ), and μ B is the baseflow DP export coefficient adjusted for temperature with an Arrhenius equation similarly to soils (Eq.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Elliott and Sorrell (2002) provide N and P losses for 'low-intensity pasture'. Notably, Caruso's (2000) reported P loss is much lower than Elliott and Sorrell's (2002).…”
Section: Pastoral Land Coverscontrasting
confidence: 57%
“…Base flow, although it does not contain high P concentrations, can act as a constant background source of P [ McDowell et al , 2001], and contribute substantially to cumulative P loads [ Maguire and Sims , 2002]. For example Caruso [2000] found base flow P exports to be 47% of the P lost from an agricultural watershed, while Hively et al [2005] found base flow P exports to be 30% of the total in a dairy farm dominated watershed. Additionally, soils exhibiting macropore flow can contribute significant P loads to the subsoil, or directly to groundwater [ Hooda et al , 1999], thus increasing the base flow P contribution, especially in tile drained watersheds.…”
Section: Dissolved Phosphorus Model Developmentmentioning
confidence: 99%